A case study: Thermophysics characterization of tropical soils extracted in the horizons HA and HB - Bento, Antonio; Picolloto, Angela Maria; Kuritza, Danilo; Baesso, Mauro Luciano; Zanuto, Vitor Santalela; Cezar, Everson; Nanni, Marcos R. (Transdisciplinary journal of engineering & science, 2024)
Thermal Wave Interferometry (TWI) technique was used to access the thermal diffusivity and thermal conductivity of soils with sandy and clayey textures from Paraná land, specifically from horizons HA (5 to 25 cm) and HB (25 to 76 cm). Experimental setup involved focusing white light on soil samples in titanium wells (100-1200 μm thick), modulated at frequencies from 0.6 to 45 Hz. Results showed that sandy soils had higher thermal diffusivity and conductivity than clayey soils. Open Photoacoustic Cell (OPC) also measured the thermal diffusivity, while TWI determined thermal conductivity ranged from 0.3 to 1 Wm⁻¹K⁻¹, and thermal diffusivity from 1 to 9 x 10⁻⁷ m²/s. Specific heat was measured using Non-Adiabatic Thermal Relaxation Calorimetry (NATRAC), revealing values between 820 to 920 J/kg·K for HA soils and 940 to 1140 J/kg·K for HB soils. Gravimetric measurements provided soil particle and bulk density data.